Cerebral Blood Flow Difference Between Acute and Chronic Tinnitus Perception: A Perfusion Functional Magnetic Resonance Imaging Study - Hu, Jinghua; Xu, Jin-Jing; Shang, Song’an; Chen, Huiyou; Yin, Xindao; Qi, Jianwei; Wu, Yuanqing (Frontiers in Neuroscience, 2021)
Purpose: The central nervous mechanism of acute tinnitus is distinct from that of chronic tinnitus, which may be associated with the difference of cerebral blood flow (CBF) perfusion in certain regions. To verify this conjecture, we used arterial spin labeling (ASL) perfusion magnetic resonance imaging (MRI) to compare the CBF alterations of patients with acute and chronic tinnitus perception. Methods: The current study included patients with chronic tinnitus (n=35), acute tinnitus (n=30) and healthy controls (n=40) who were age, sex, education-matched. All participants underwent MRI scanning and then ASL images were obtained to measure CBF of the entire brain and analyze the differences between groups as well as the correlations with tinnitus characteristics. Results: Chronic tinnitus group showed increased z-CBF in the right superior temporal gyrus (STG) and superior frontal gyrus (SFG) when compared with acute tinnitus patients. Further connectivity analysis found enhanced CBF connectivity between the right STG and right fusiform gyrus (FG), right SFG and left middle occipital gyrus (MOG) as well as right parahippocampal gyrus (PHG), left STG and right FG. Moreover, compared with acute tinnitus, the normalized z-CBF of right STG was positively correlated with tinnitus distress in chronic tinnitus patients (r=0.440, p=0.013). Conclusions: Our results confirmed that the CBF changes in some brain regions were different between acute and chronic tinnitus perception, which was correlated with certain tinnitus characteristics. This is of great value to the further research on chronic perception of tinnitus and ASL has a good application prospect in measurement of CBF.